Analisis Faktor-Faktor yang Mempengaruhi Profitabilitas pada PT Bank BRI Syariah Tbk - Jilda Khoirunnisaa; Dimas Sumitra Danisworo; Yudha Trishananto (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to determine the effect of mudharabah financing (X1), musyarakah financing (X2), murabahah receivables (X3), and BOPO (X4) on profitability as measured using Return On Aset (ROA) (Y) PT Bank BRI Syariah Tbk. In this study, data was taken in the form of Annual Financial Report data for the 2016-2019 period stipulated by Bank Indonesia. The analysis ini this study includes descriptive statistical test using IBM SPSS 20 analysis tool. The results showed that simultaneously mudharabah financing, musyarakah financing, murabahah receivablesm and BOPO had an effect on ROA. Partially, musyarakah financing has a significant positive effect on ROA, BOPO has a significant negatif effect on ROA, and mudharabah financing and murabahah receivables have no significant effect on ROA.